KEARIFAN LOKAL PALEMBANG SEBAGAI DAYA TARIK WISATA - Yusro Hakimah; Yun Suprani (JURNAL KOMPETITIF, 2021)
Palembang is famous for pempek. In addition, the city of Palembang has a unique characteristic, during the celebration of Independence Day, namely telok abang and telok ukan. However, lately, the commemoration of Independence Day in Palembang has not been as festive. telok abang and telok ukan increasingly difficult to find. The research conducted is descriptive qualitative research, namely research that describes the phenomenon of almost extinction of telok abang and telok ukan. Which is local wisdom as a tourist attraction in Palembang. Cultural tourism attraction is one of the superior values that can be developed by the Regional Government. Local wisdom can be included in the attraction of cultural tourism. local wisdom should be preserved and maintained. In local wisdom there is a historical value of the nation's personality. Maintained local wisdom will provide economic value for the community